Aspectual substitution: verbal change in New Testament quotations of the Septuagint - Freney, Samuel J. (Studies in biblical Greek, 2020)
"New Testament authors quote the Old Testament on hundreds of occasions, and frequently quote the Septuagint. Often, however, they make alterations to the original text. This study examines quotations where the NT author changes the tense-form of a verb in quoted material, substituting one aspectual value for another. This change is often made in furtherance of a typological, prophetic, or theological connection. Taking into account various models of the verb in Koine Greek, including tenseless and aspect-prominent proposals, this study employs contrastive substitution to analyze the significance of aspectual substitution in quotations, concluding that the Future tense-form encodes perfective aspect and is marked for future temporal reference. Of particular interest to anyone who has followed the Greek verbal aspect discussion in recent decades, this volume contributes to the discussion by testing various verbal theories on instantiated choices and their rhetorical effects. In addition to linguistic study, this study also interacts with the character of the Septuagint text(s), and how NT authors use OT texts in quotation and for theological construal"--